Mobile Health Information Security in the eHealth Cloud (Journal of The Colloquium for Information Systems Security Education, 2017)
With the healthcare industry facing a new reality, healthcare applications are steadily impacting the mobility and security of how caregivers and hospitals are authorized to access vital information. In this Chapter, a proposed privacy-preserving EHR system using ciphertext-multi authority attribute-based encryption (CPMA-ABE) will be built. In this system, patients can encrypt their EHRs and store them on semi-trusted cloud servers such that servers do not have access to sensitive EHR contexts. Meanwhile patients maintain full control over access to their EHR files, by assigning fine-grained, attribute-based access privileges to selected data users, while different users can have access to different parts of their EHR. In addition, security issues for mobile health are discussed as well.
Keywords: cloud computing; electronic health records; security; privacy; role based access control; mobile health; encryption